2020
DOI: 10.3390/f11080864
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and Water Relation Responses to Ozone and Water Stress in Seedlings of Three Oak Species with Different Adaptation Strategies

Abstract: The impact of global changes on forest ecosystem processes is based on the species-specific responses of trees to the combined effect of multiple stressors and the capacity of each species to acclimate and cope with the environment modification. Combined environmental constraints can severely affect plant and ecological processes involved in plant functionality. This study provides novel insights into the impact of a simultaneous pairing of abiotic stresses (i.e., water and ozone (O3) stress) on the responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In Q. ilex, this relationship was not significant, suggesting a higher tolerance and different strategy to face drought. Similarly, drought reduced light-saturated rate of photosynthetic carbon uptake and stomatal conductance more in QR and QP than in QI (Cocozza et al 2020). A significant interaction effect between these oak species and drought, as well with other stressors, such as ozone, was observed by Hoshika et al (2018) and Cotrozzi et al (2016), indicating different strategies among the three species.…”
Section: Consistency Between Nir-camera Vis and Morpho-physiological Stress Indicesmentioning
confidence: 90%
“…In Q. ilex, this relationship was not significant, suggesting a higher tolerance and different strategy to face drought. Similarly, drought reduced light-saturated rate of photosynthetic carbon uptake and stomatal conductance more in QR and QP than in QI (Cocozza et al 2020). A significant interaction effect between these oak species and drought, as well with other stressors, such as ozone, was observed by Hoshika et al (2018) and Cotrozzi et al (2016), indicating different strategies among the three species.…”
Section: Consistency Between Nir-camera Vis and Morpho-physiological Stress Indicesmentioning
confidence: 90%
“…The magnitude and timing of drought stress responses were species-specific, which may be related to differences in species hydraulic traits. Oak has a deep reaching root system and may thus be able to maintain water uptake during low precipitation periods 24,29,45 , while its water saving behavior (oak is isohydric 35,36 ) may have helped to avoid xylem cavitation during peak drought periods 21 . In contrast, ash has roots mainly restricted to upper soil layers and is thus more dependent on precipitation than oak 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we reconstruct the stress exerted by this unprecedented event and compare it to past (single) drought events based on tree-ring records from dominant tree species in the Leipzig floodplain forest, one of the few remaining and thus highly protected floodplain forests in Central Europe 33,34 . The studied species span a gradient in stomatal control and root system architecture, with Quercus robur L. (hereafter oak) having isohydric behavior 35,36 and a deep reaching heart-sinker root system 24,25 , Acer pseudoplatanus L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies have evidenced that provenances and species originating from drier climate perform better under drought condition (Pšidová et al 2015, Wang et al 2017. For instance, investigation of the drought tolerance of Quercus ilex L., Q. pubescens Willd., and Q. robur L., showed that the Mediterranean oak species, despite a reduction of light-saturated net photosynthesis (Cocozza et al 2020), maintained higher photosynthetic activity compared to Central-European oak species (Früchtenicht et al 2018).…”
Section: Introductionmentioning
confidence: 93%